Remotely Light‐Powered Soft Fluidic Actuators Based on Plasmonic‐Driven Phase Transitions in Elastic Constraint. Issue 51 (4th November 2019) - Meder, Fabian; Naselli, Giovanna Adele; Sadeghi, Ali; Mazzolai, Barbara
Abstract: Materials capable of actuation through remote stimuli are crucial for untethering soft robotic systems from hardware for powering and control. Fluidic actuation is one of the most applied and versatile actuation strategies in soft robotics. Here, the first macroscale soft fluidic actuator is derived that operates remotely powered and controlled by light through a plasmonically induced phase transition in an elastomeric constraint. A multiphase assembly of a liquid layer of concentrated gold nanoparticles in a silicone or styrene–ethylene–butylene–styrene elastic pocket forms the actuator. Upon laser excitation, the nanoparticles convert light of specific wavelength into heat and initiate a liquid‐to‐gas phase transition. The related pressure increase inflates the elastomers in response to laser wavelength, intensity, direction, and on–off pulses. During laser‐off periods, heating halts and condensation of the gas phase renders the actuation reversible. The versatile multiphase materials actuate—like soft "steam engines"—a variety of soft robotic structures (soft valve, pnue‐net structure, crawling robot, pump) and are capable of operating in different environments (air, water, biological tissue) in a single configuration. Tailored toward the near‐infrared window of biological tissue, the structures actuate also through animal tissue for potential medical soft robotic applications. Abstract : Light‐powered fluidic actuators applicable in microfluidics and soft robots in various environments are introduced. The actuation is based on a plasmonically induced phase transition in an elastic pocket and it works much like a "steam engine" but it is entirely soft and light‐driven.